Bacteriophage effectively kills multidrug resistant Staphylococcus aureus clinical isolates from chronic rhinosinusitis patients. Issue 3 (14th December 2017) - Zhang, Guimin; Zhao, Yin; Paramasivan, Sathish; Richter, Katharina; Morales, Sandra; Wormald, Peter‐John; Vreugde, Sarah
Abstract : Background: Bacteriophage (phage) therapy has been proposed as an alternative to antibiotics. Phages have been shown to kill antibiotic resistant Staphylococcus aureus strains; however, it is unknown whether stress‐induced antibiotic tolerance affects S. aureus susceptibility to phages. Our objective was to determine the effectiveness of 2 phages currently in clinical development, against antibiotic‐resistant and induced antibiotic‐tolerant clinical S. aureus isolates. Methods: Antibiotic tolerant S. aureus strains were induced by incubation with increasing concentrations of gentamicin, mupirocin, and ciprofloxacin over time and their susceptibility to 2 clinically relevant phages (Sa83 and Sa87) was assessed. In addition, phage susceptibility was tested in relation to the antibiotic sensitivity of 65 clinical S. aureus isolates, harvested from the sinonasal cavities of chronic rhinosinusitis (CRS) patients. Phage sensitivity was assessed using a plaque spot assay and by measuring optical density values to observe planktonic S. aureus growth in the presence of the phage. Alamar Blue assays were used to assess biofilm viability after phage treatment. Results: Frequency of antibiotic resistance amongst clinical S. aureus isolates was 90.7% (59/65) with 13 of 65 (20.0%) identified as multidrug‐resistant. Tolerance to gentamicin, mupirocin, and ciprofloxacin was rapidly induced by incubation with increasing concentrations of respective antibiotics. There was no significant difference in phage sensitivity between antibiotic‐sensitive and resistant/tolerant S. aureus clinical isolates in planktonic and biofilm form. Conclusion: Clinical S. aureus isolates from CRS patients have a high (20%) incidence of multidrug resistance. Antibiotic resistance or tolerance did not affect phage susceptibility of those isolates.